Measuring respondent burden in Nigeria: A case study of Central Bank of Nigeria enterprise surveys - Ibrahim Adamu; Ismaila S. Sabi; Sani Bawa (CBN Journal of Applied Statistics, 2014)
This paper uses diffusion indices, percentages and reported time spent to measure the respondent burden in survey of foreign assets and liabilities (SOFAL) and business expectations survey (BES). The results show that respondents found it easy but time consuming to complete the SOFAL questionnaire with an average of 24 hours spent in collecting information and over 2 hours to fill the questionnaire. In contrast, respondents found it much easier and quicker to complete the BES questionnaire, spending an average of 47 minutes to collect relevant information from their records and another 36 minutes to complete the questionnaire. The paper identified problems of documentation, cumbersomeness of the survey instruments and lack of motivation of the respondents as main issues of concern.
Keywords: Y10; 330; Respondent burden; Business expectation survey; survey of foreign assets and liabilities